The Thermal Biology of Takydromus kuehnei Indicates Tropical Lizards From High Elevation Have Not Been Severely Threatened by Climate Change - Tao, Shiang; Cheng, Kunming; Li, Xinghan; Han, Xingzhi; Wang, Jichao; Zheng, Rongquan; Sun, Baojun (Frontiers in Ecology and Evolution, 2021)
Climate change poses different threats to animals across latitudes. Tropical species have been proposed to be more vulnerable to climate change. However, the responses of animals from tropical mountains to thermal variation and climate change have been scarcely studied. Here, we investigated the thermal biology traits of a tropical lizard (Takydromus kuehnei) distributed at high elevations (>950m) and evaluated the vulnerabilities of T. kuehnei by thermal biology traits, thermal safety margin, and thermoregulatory efficiency. The average active body temperatures of T. kuehnei in the field were 26.28 ℃ and 30.65 ℃ in April and June, respectively. The selected body temperature was 33.23 ℃, and the optimal temperature for locomotion was 30.60 ℃. The critical thermal minimum and critical thermal maximum temperatures were 4.79 ℃ and 43.37 ℃, respectively. Accordingly, the thermal safety margin (1.23℃) and thermoregulatory efficiency (1.23℃) predicted that T. kuehnei distributed in tropical mountains were not significantly depressed by environmental temperatures. This study implies that high-elevation species in tropical regions may not be severely threatened by climate change and highlights the importance of thermal biology traits in evaluating the vulnerability of species to climate change.